Skeleton composition versus stable process systems in Eden. (15th July 2016) - DIETERLE, M.; HORSTMEYER, T.; LOOGEN, R.; BERTHOLD, J.
Abstract: We compare two inherently different approaches to implement complex process systems in Eden: stable process systems and a compositional approach. A stable process system is characterised by handling several computation stages in each of the participating processes. Often, processes communicate using streams of data, change behaviour with the different computation phases, and more often than not, exactly one process is allocated to each processor element. In contrast, a complex process system can also be achieved by skeleton composition of a number of elementary skeletons, such as parallel transformation, reduction, or special communication patterns. In a compositional implementation, each computation phase leads to a new set of interacting processes. When implementing complex parallel algorithms, skeleton composition is usually easier and more flexible, but has a larger overhead from additional process creation and communication. We present case studies of different parallel application kernels implemented as stable systems and using composition in Eden, including a comprehensive description of Eden's features. Our results show that the compositional performance loss can be alleviated by co-locating processes which directly communicate, and by using Eden's remote data concept to enable such direct communication. Moreover, Eden's parallel runtime system handles communication between co-located processes in an optimised way. EdenTV visualisations of execution traces are invaluable to analyse program characteristics and for targeted optimisations towards better process placement and communication avoidance.